2011
DOI: 10.1007/s10900-011-9452-9
|View full text |Cite
|
Sign up to set email alerts
|

Using Survey Results Regarding Hepatitis B Knowledge, Community Awareness and Testing Behavior Among Asians to Improve the San Francisco Hep B Free Campaign

Abstract: Asians are disproportionately affected by chronic hepatitis B (HBV) infection and its fatal consequences. The Hep B Free campaign was launched to eliminate HBV in San Francisco by increasing awareness, testing, vaccination and linkage to care. The campaign conducted 306 street intercept and telephone interviews of San Francisco Asians to assess current levels of HBV knowledge, testing behaviors and effectiveness of existing campaign media materials. One-third of respondents ranked HBV as a key health issue in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 25 publications
(28 reference statements)
1
41
0
Order By: Relevance
“…This misperception is also reported in Asian HBV patients [18,19,21] and general public in Singapore, San Francisco, Washington and Australia [23-25]. Such misperceptions could evoke anxiety in individuals with HBV and may create a barrier in their social interaction for fear of transmitting the virus to others.…”
Section: Discussionmentioning
confidence: 79%
“…This misperception is also reported in Asian HBV patients [18,19,21] and general public in Singapore, San Francisco, Washington and Australia [23-25]. Such misperceptions could evoke anxiety in individuals with HBV and may create a barrier in their social interaction for fear of transmitting the virus to others.…”
Section: Discussionmentioning
confidence: 79%
“…First, the San Francisco Bay Area has a high density of Asian immigrants with a reported HBV prevalence of 9–15% (4, 38, 39), and as such, providers may have increased familiarity with HBV management in this population. Additionally, a large grassroots campaign aimed at improving HBV awareness in the Asian American community has been ongoing in this region and an analysis of the impact of San Francisco Hepatitis B Free Campaign found that a high proportion of Asian respondents were familiar with hepatitis B (90%) and that almost half reported an increase in hepatitis B awareness within their community (40). These factors are likely to have played a role in the higher rates of HBV disease monitoring among Asian American patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that lack of knowledge about HBV transmission and its consequences leads to low levels of vaccination and screening. A number of initiatives have been implemented to raise the uptake of vaccination and screening in the Asian American population, with some success 1114. To our knowledge, no studies have specifically evaluated the level of awareness among Asian American individuals of current potent antiviral therapies available for the treatment of CHB.…”
Section: Introductionmentioning
confidence: 99%